Deficiency of the T cell regulator Casitas B-cell lymphoma-B aggravates atherosclerosis by inducing CD8+ T cell-mediated macrophage death. (17th November 2018) - Seijkens, Tom T P; Poels, Kikkie; Meiler, Svenja; van Tiel, Claudia M; Kusters, Pascal J H; Reiche, Myrthe; Atzler, Dorothee; Winkels, Holger; Tjwa, Marc; Poelman, Hessel; Slütter, Bram; Kuiper, Johan; et al.
Abstract: Aims: The E3-ligase CBL-B ( Casitas B-cell lymphoma-B ) is an important negative regulator of T cell activation that is also expressed in macrophages. T cells and macrophages mediate atherosclerosis, but their regulation in this disease remains largely unknown; thus, we studied the function of CBL-B in atherogenesis. Methods and results: The expression of CBL-B in human atherosclerotic plaques was lower in advanced lesions compared with initial lesions and correlated inversely with necrotic core area. Twenty weeks old Cblb −/− Apoe −/− mice showed a significant increase in plaque area in the aortic arch, where initial plaques were present. In the aortic root, a site containing advanced plaques, lesion area rose by 40%, accompanied by a dramatic change in plaque phenotype. Plaques contained fewer macrophages due to increased apoptosis, larger necrotic cores, and more CD8 + T cells. Cblb −/− Apoe −/− macrophages exhibited enhanced migration and increased cytokine production and lipid uptake. Casitas B-cell lymphoma-B deficiency increased CD8 + T cell numbers, which were protected against apoptosis and regulatory T cell-mediated suppression. IFNγ and granzyme B production was enhanced in Cblb −/− Apoe −/− CD8 + T cells, which provoked macrophage killing. Depletion of CD8 + T cells in Cblb −/− Apoe −/− bone marrow chimeras rescued the phenotype, indicating that CBL-B controls atherosclerosis mainly through its function in CD8 + T cells. Conclusion: Casitas B-cell lymphoma-B expression in human plaques decreases during the progression of atherosclerosis. As an important regulator of immune responses in experimental atherosclerosis, CBL-B hampers macrophage recruitment and activation during initial atherosclerosis and limits CD8 + T cell activation and CD8 + T cell-mediated macrophage death in advanced atherosclerosis, thereby preventing the progression towards high-risk plaques.